Addressing Gender-Based Violence: Comparative Analysis of International Legal Frameworks and Practices - Stince Sidayang; Muhammad Julianto Sumanta; Candra Kirana Putri Calya; Sabil Mokodenseho (Eastasouth Institute, 2023)
Gender-based violence (GBV) is a global issue that violates human rights and impedes social development. This research paper presents a comparative analysis of the international legal framework and practices relating to GBV in Indonesia. Through a qualitative research approach, including document analysis, comparative legal analysis, and case studies, this research explores the alignment of Indonesia's legal framework with international standards and examines initiatives and practices implemented in Indonesia to address GBV. The research identifies gaps, challenges, and potential solutions, providing insights for policymakers, practitioners, and advocates working to combat gender-based violence in Indonesia and other similar contexts.